Coronary Artery Dissection and Myocardial Infarction With Nonobstructed Coronary Arteries: Insights From a UK Nationwide Autopsy-Based Registry—Brief Report. Issue 5 (27th April 2023) - Ciliberti, Giuseppe; Westaby, Joseph; Papadakis, Michael; Behr, Elijah R.; Sharma, Sanjay; Finocchiaro, Gherardo; Sheppard, Mary N.
Abstract : Background: Spontaneous coronary artery dissection (SCAD) and myocardial infarction with nonobstructed coronary arteries (MINOCA) are increasingly recognized causes of acute coronary syndrome and potentially of sudden cardiac death (SCD). SCAD has been correlated to coronary fibromuscular dysplasia (FMD), but the prevalence of SCAD and FMD among SCD victims is unclear. Therefore, we sought to assess characteristics of decedents with SCAD found at autopsy and to compare their clinical and pathological profile with MINOCA victims. Methods: We reviewed a database of 5325 consecutive cases of SCDs referred to our cardiac pathology center between 1994 and 2017. Results: We identified 18 (0.3%) cases with SCAD and 37 (0.7%) with MINOCA. No signs of coronary FMD were found among SCAD and MINOCA victims. Compared to MINOCA, SCAD decedents were mostly females (78% versus 38%, P =0.006) and SCD occurred during peripartum more frequently in SCAD rather than MINOCA female victims (28% versus 3%, P =0.012) Infarcted myocardium was identified in all cases of MINOCA but only in 5 (28%) of SCAD decedents ( P <0.001). Premortem cardiac symptoms were present in 100% of SCAD and 49% of MINOCA victims ( P <0.001); substances use or abuse was reported in none of SCAD versus 43% of MINOCA decedents ( P =0.001). Conclusions: SCAD and MINOCA are rare causes of SCD. At autopsy, coronary FMD is not present among SCAD victims. Compared to MINOCA, SCAD victims are more frequently females, are linked to pregnancy, and always experienced premortem cardiac symptoms. Among MINOCA victims' substance use or abuse is common.